Banning Bottled Water in Concord, MA: How an Apolitical Commodity Became Political - Begg, Rachel (Université d'Ottawa / University of Ottawa, 2014)
This thesis paper explores how various actors gathered around bottled water when a ban was put into place in Concord, Massachusetts. The objective has been to answer the following questions: How does an apolitical commodity become a political one? Specifically, how does bottled water move from being an apolitical commodity to become a highly political one? What does this mean for environmental politics? I situate my theoretical approach within Martha Kaplan’s research with fountains and coolers. I use Bruno Latour to show in which ways this ban became a matter of concern, as well as how the ban and the plastic bottle are actors. I conducted fieldwork in Concord and I interviewed participants. My findings reveal that the ban brought meanings to the surface and challenged them or supported them in various ways. The discussions turned from the impact of bottled water on our environment to the political impact of bottled water companies and large corporations on local Concord issues.
Keywords: water; bottled water; commodity; Concord; local activism; ban; environmental activism; activism; environmental politics; tap water; fountains